Deteksi Fraud pada LKM Syariah: Tinjauan Internal Control dan Budaya Organisasi - Cinda Nongfasya Ruwary; Mukhtaruddin Mukhtaruddin (GLOBAL SCIENTS PUBLISHER, 2026)
The sustainability of Islamic Microfinance Institutions (IMFIs) is increasingly threatened by fraud, yet existing mitigation strategies often over-rely on